2021
DOI: 10.1136/bmjopen-2021-050818
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychological profiles based on perceived health clustering in patients with cardiovascular disease: a longitudinal study

Abstract: ObjectivesPsychological well-being and sociodemographic factors have been associated with cardiovascular health. Positive psychological well-being research is limited in the literature; as such, this study aimed to investigate how patients with cardiovascular disease could be classified according to their perceived mental and physical health, and to identify positive psychological profiles based on this classification and test their stability over time.Design and settingLongitudinal study with patients from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Moreover, as described by prior works (Castillo-Mayén, Luque, Rubio, et al, 2021; Modica et al, 2019; Sandberg et al, 2015), functional coping strategies, affective balance, and stronger intention to adopt healthier behaviors were found determinant in achieving better cardiovascular health. Overall, this finding extends the current body of knowledge that already established strong relationships between positive psychological profiles and the adoption of healthier behaviors, and how these relations are longitudinally associated with better perceived cardiovascular health (Adorni et al, 2022; Castillo-Mayén, Luque, Rubio, et al, 2021; Roshanaei-Moghaddam et al, 2009). In addition to this, the present work not only sheds light on the indirect role of psychological and behavioral factors in the longitudinal improvement of HRQoL, but it may also provide future preventive intervention programs with crucial components to be targeted in order to enhance patients’ self-management skills following a cardiac event.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Moreover, as described by prior works (Castillo-Mayén, Luque, Rubio, et al, 2021; Modica et al, 2019; Sandberg et al, 2015), functional coping strategies, affective balance, and stronger intention to adopt healthier behaviors were found determinant in achieving better cardiovascular health. Overall, this finding extends the current body of knowledge that already established strong relationships between positive psychological profiles and the adoption of healthier behaviors, and how these relations are longitudinally associated with better perceived cardiovascular health (Adorni et al, 2022; Castillo-Mayén, Luque, Rubio, et al, 2021; Roshanaei-Moghaddam et al, 2009). In addition to this, the present work not only sheds light on the indirect role of psychological and behavioral factors in the longitudinal improvement of HRQoL, but it may also provide future preventive intervention programs with crucial components to be targeted in order to enhance patients’ self-management skills following a cardiac event.…”
Section: Discussionsupporting
confidence: 51%
“…This inference may find its reliability not only after controlling the path analysis for baseline HRQoL scores, but also providing evidence of significant improvements in HRQoL over 18 months. Moreover, as described by prior works (Castillo-Mayén, Luque, Rubio, et al, 2021; Modica et al, 2019; Sandberg et al, 2015), functional coping strategies, affective balance, and stronger intention to adopt healthier behaviors were found determinant in achieving better cardiovascular health. Overall, this finding extends the current body of knowledge that already established strong relationships between positive psychological profiles and the adoption of healthier behaviors, and how these relations are longitudinally associated with better perceived cardiovascular health (Adorni et al, 2022; Castillo-Mayén, Luque, Rubio, et al, 2021; Roshanaei-Moghaddam et al, 2009).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The instrument consists of 20 items and uses a Likert scale of five points, where 1 = "totally disagree" and 5 = "strongly agree": 10 items (e.g., "excited") measure positive affect and 10 items (e.g., "worried") measure negative affect. The Cronbach's alpha coefficients in the original study were 0.87 and 0.86, respectively; in a Spanish sample of patients with CVDs, the reliabilities of the measure were 0.88 and 0.80, respectively [49]. In the current sample, the reliability for positive affect was α = 0.89 at baseline and α = 0.91 at post-test 3, and for negative affect, the reliability was α = 0.87 at baseline and α = 0.89 at post-test 3.…”
Section: Measures 231 Positive and Negative Affectmentioning
confidence: 85%
“…However, these characteristics should be taken into account in further studies, as low socioeconomic status may be related to poorer health outcomes. In this regard, a recent study found that patients with CVDs who reported lower income were included in a cluster of low self-reported mental and physical health, which in turn was associated with a profile of poorer psychological wellbeing [49]. Therefore, patients with lower socioeconomic status may benefit even more from these psychological interventions.…”
Section: Limitations and Future Researchmentioning
confidence: 99%